Piperacillin-Tazobactam as an Adjuvant in the Mechanical Treatment of Patients with Periodontitis: A Randomized Clinical Study - Dolores Hurtado-Celotti; Natalia Martínez-Rodríguez; Pedro Luis Ruiz-Sáenz; Cristina Barona-Dorado; Juan Santos-Marino; José María Martínez-González (MDPI AG, 2022)
In this study, the aim was to evaluate the effects of the adjuvant piperacillin-tazobactam solution in the mechanical treatment of periodontitis. A single-blind split-mouth randomized study, it included 24 participants. All of them presented periodontitis stage III according to the 2018 World Workshop classification and the presence of at least one of the following periodontal pathogens: Aggregatibacter actinomycetemcomitans; Porphyromona gingivalis; Treponema denticola; Tannerella forsythia; Prevotella intermedia. The study established two groups: a control group (SRP: scaling and root planing) and a test group (SRP plus local piperacillin-tazobactam). The final recruitment included 11 women (45.8%) and 13 men (54.2%). The age range was between 25 and 72 years, and the mean age was 57 ± 10.20 years. Clinical controls were performed at 2 weeks, 3 months, and 6 months, repeating the SRP and applying the piperacillin-tazobactam solution again at the 3-month appointment. The clinical attachment level decreased by a mean of 2.13 ± 0.17 mm from the baseline to 6 months in the test group versus 1.63 ± 0.18 mm in the control group. The mean probing pocket depth decreased from 1.32 ± 0.09 mm in the test group, versus from 0.96 ± 0.14 mm on the control side. The plaque index in the test group decreased by 0.46 ± 0.04, while it decreased by an average of 0.31 ± 0.04 in the control group. In conclusion, the local use of piperacillin-tazobactam as complementary therapy produces better clinical results in patients with periodontitis. However, these results are not maintained over time, and so a more persistent local application is necessary.